Effects of exposing Japanese quail eggs to a low dose of gamma radiation and in ovo feeding by two sources of trace elements on embryonic development activities - Mahmoud H. Hatab; Wei Chen; Khaled Abouelezz; Mahmoud Elaroussi; Aml Badran; Khairy Zoheir; Esteftah El-komy; Shijun Li; Abdelmotaleb Elokil (Poultry Science, 2024)
ABSTRACT: The present study investigated the influence of exposing quail eggs to low-dose gamma radiation (GR) and in ovo feeding with 2 sources of a mixture of trace elements (Zn, Fe, and Cu), including sulfate (TES) and loaded with montmorillonite (TEM), on embryonic development activities and prehatch quality. A total of 960 eggs on the seventh day of incubation were randomly divided into 6 groups (160 eggs/group) with 4 replicate of 40 eggs in each. A 3 × 2 factorial arrangement experiment was performed and included 3 sources in ovo feeding with a mixture of trace elements (Zn, Fe, and Cu), including 0 mg/egg, 50 mg TES/egg, and 50 mg TEM/egg with egg irradiation using 0 and 0.2 Gy from GR. Eggs injected with 50 mg TEM/egg and exposed to 0.2 Gy from GR (TEM/GR) was significantly (P ≤ 0.05 and 0.01) higher in hatchability, hatch body weight, and relative organ weight (liver, gizzard, proventriculus, heart, and intestine). The obtained results indicated significant (P ≤ 0.05) decreased in the serum concentration of malondialdehyde (MDA) in TEM/GR group. There was significant (P ≤ 0.05) increased of catalase (CAT) activity and the concentrations of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) in TEM/GR group; however; total antioxidant capacity (T-AOC) was significant (P ≤ 0.05) increased in CT/GR group. Serum concentrations of immunoglobulin M (IgM) (P ≤ 0.05) and tumor necrosis factor-alpha (TNF-α) were increased in the TEM/CR group; the concentration of transforming growth factor beta (TGF-β) significant (P ≤ 0.05) increased in the TEM/GR group; and interleukins (IL6 and IL10) showed no significant differences among the groups. Our results showed increase in thyroxine and myostatin concentrations with TES/CR and CT/GR of our study groups, respectively. The relative mRNA expression levels of the GH, IGF-1, and Fas cell surface death receptor (FAS) genes were significantly (P ≤ 0.05 and 0.01) upregulated in the liver tissue of the TEM/GR group compared with the other groups. In conclusion, TEM/GR was the best treatment for improving prehatch quality, increasing serum antioxidant enzyme activities, and promoting the expression of growth and immune genes in fertilized quail eggs.